Comparison of Dental mineralization stages using orthopantomogram (OPG) and Skeletal maturation using hand wrist radiographs during Pubertal growth period - A. Anandkumar, A. Anandkumar; Nandakumar, G.Dinesh; Anitha, Anitha; Agasthiya, Agasthiya; Jeevan, Gerard; Muhammed Hussain, Siddique Sha (Journal of Neonatal Surgery, 2025)
Introduction: Skeletal maturation is assessed from the analysis of cervical vertebral maturation using lateral cephalograms and analysis of bones in the Hand and wrist regions using hand wrist radiographs. which give an insight into the underlying dental and skeletal conditions of malocclusion and to some extent the skeletal maturation of the individual through cervical vertebral maturation and thereby facilitate the determination of the dental age. Aims and Objectives: The present study aims to determine the correlation between dental mineralisation stages and skeletal maturation in determining the pubertal growth period by studying OPG and hand wrist of 600 samples in South Indian population. Materials and methods: A total of 600 samples were selected in the age group between 7 to 17 years. OPG and Hand-wrist radiographs were taken using SIRONA Orthophos XG 5 DS/Ceph for all the samples the skeletal maturation and dental mineralization stages were analysed. The means of the chronologic ages for both the sexes in three periods of skeletal maturation was analysed by 2-way analysis of variance (ANOVA) and post hoc tukey test. And the analysis of ordinal multinomial logistic regression to evaluate the which teeth had the mineralization association to skeletal maturation. Results: Mineralization stages of teeth at the Peak of Pubertal growth period for boys were seen in mandibular canine stage G and second molars. For girls, the stage G were seen in mandibular canine and first premolar, other teeth with higher percentage of distribution was seen in mandibular second molar but as the tooth was not statistically significant it was neglected. Conclusion: It is concluded that dental mineralization stages studied from Orthopantomogram (OPG) a routine diagnostic tool can be used to determine the skeletal maturation of the individual thereby reducing the additional radiation exposure to the patient.